AB1155 Depression and suicidality are common in psoriatic arthritis and axial spondyloarthritis, and rates are comparable to those in psoriasis. (15th June 2017) - Sheahan, A; Suruki, R; Taylor, PC; Sloan, VS
Abstract : Background: Depression and suicidality are well-described comorbidities in psoriasis (PSO). The prevalence of these comorbidities in psoriatic arthritis (PsA) and axial spondyloarthritis (axSpA) is less well described. Objectives: To assess the prevalence of depression and suicidality in PsA and axSpA in the recent literature, and compare rates to PSO. Methods: For PsA and axSpA, we evaluated the recent English-language literature identified through a PubMed search; we used a recent review and performed a targeted review of the period since the publication in order to establish the rates for PSO for comparison. 1 Review articles were also examined to identify key publications. Results: Rates of depression in PSO vary widely, depending on the outcome definition and method of ascertainment. Dowlatshahi et al. reported a pooled rate of 9.0–55.0%, with rates from the literature after the review period ranging from 9.0–39.8%. Rates for suicidality also varied widely, with 2.5–17.3% of patients (pts) reporting suicidal ideation. The limited data available provide ranges for depression in PsA of 3.4–28.6%, and in axSpA of 3.1–44.0%. The single study that differentiated between ankylosing spondylitis (AS) and non-radiographic (nr)-axSpA did not identify a difference between the two groups. 2 Very limited data existed on suicidality in PsA and axSpA. For PsA, the incidence rates (IR) of suicidal ideation, attempts, and suicide per 1000 person-years in the UK were 0.4, 1.3, and <0.001, respectively; 3 no prevalence data were identified. In a study in China, 2.5% of pts with axSpA reported a past suicide attempt, 4 while a study in Turkey found 9.6% of pts with AS had thoughts of suicide in the past year, but without plans. 5 Depending on the study, different definitions and tools were used to assess depression (eg. HADS, ICD9, antidepressant use), and even when the same tool was used, different cutoffs for defining depression were implemented (eg. cutoff for HADS ranged from ≥5 to ≥11), making comparisons across studies difficult. In a large observational study of AS with matched controls, the IR of depression per 1000 pt-years was 5.48 in AS versus 3.29 without AS, risk ratio 1.63. 6 Conclusions: Although data are limited, rates of depression and suicidality in PsA and axSpA are comparable to those in PSO. Comparisons between studies and diseases are challenging due to a lack of standardized assessment tools and definitions of depression and suicidality. There are almost no data for nr-axSpA, which unlike AS has no gender predominance. Given that depression in PSO pts is more common in women, 7 understanding the relative prevalence in AS versus nr-axSpA would be important. Generating additional data regarding the impact of depression and suicidality in PsA and axSpA should increase awareness among treating physicians. References: Dowlatshahi EA. J. Invest Dermatol 2014;134:1542–51. Klic GE. Medicine (Baltimore) 2014;93:e337. Hagberg KW. Mod Rheumatol 2016;26:774–9. Chan CY. Int J Rheum Dis 2014; doi:10.1111/1756-185X.12456. Saygin C. Clin Exp Rheumatol 2015;33(6 Suppl 94):S30–5. Shen CC. J Rheumatol 2016;43:625–31. Lamb RC. Br J Dermatol 2016; doi:10.1111/bjd.14833. Disclosure of Interest: A. Sheahan Employee of: UCB Pharma, R. Suruki Employee of: UCB Pharma, P. Taylor: None declared, V. Sloan Employee of: UCB Pharma